Analysis Of Home Industry-Based Umkm Development From A Maslahah Perspective (Case Study: Monik Bread In Kualuh Hulu District) - Khairani, Khairani; Lubis, Fauzi arif; Harahap, Muhammad Ikhsan (Moneter: Jurnal Keuangan dan Perbankan, 2025)
This study aims to analyze the development of Micro, Small, and Medium Enterprises (MSMEs) based on home industry from the Maslahah perspective, with a case study on the monik bread business in Kualuh Hulu District. The results of this study indicate that the existence of this home industry can create jobs and improve the welfare of the surrounding community. With the maslahah approach, this study is used to assess the extent to which this business provides benefits from both basic needs (dharuriyah), complementary (hajiyyah), and perfecting (tahsiniyyah) aspects. In addition, this study also uses a business model canvas (BMC) analysis to evaluate the monik bread business model by looking at customer segments, value propositions, distribution channels, customer relationships, sources of income, resources, main activities, main partnerships, and cost structures. The research method used is qualitative research with interview techniques, observation, and documentation of business owners. The results of the study show that the development of the Roti Monik business not only contributes to local economic growth, but also fulfills maslahah values, such as opening up job opportunities, increasing income, and maintaining the quality of halal and thayyib products. Through the implementation of BMC, this business is able to optimize its resources and activities so that the business model being run is effective and sustainable.